1998
DOI: 10.1118/1.598413
|View full text |Cite
|
Sign up to set email alerts
|

Optimum tube voltage for chest radiographs obtained by psychophysical analysis

Abstract: Many kinds of x-ray films having various characteristic curves have been developed for chest radiographs. In general, a phototiming device for determination of a mAs value which gives a proper exposure has been used for a chest radiography. For each film, however, the x-ray tube voltage has been determined by the subjective evaluation of radiologists or radiological technologists. In this paper, we propose a new method for determining the optimum tube voltage for chest radiographs using psychophysical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Kanamori proposed psychophysical methods and presented a psychophysical analysis in his article [5]. In 1998, Asai et al presented psychophysical analysis for determining the optimum tube voltage for chest radiographs [10]. The group proposed the method as an objective evaluation that does not depend on the subjective evaluation of the radiologist or radiological technologist, as is the case with ROC analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Kanamori proposed psychophysical methods and presented a psychophysical analysis in his article [5]. In 1998, Asai et al presented psychophysical analysis for determining the optimum tube voltage for chest radiographs [10]. The group proposed the method as an objective evaluation that does not depend on the subjective evaluation of the radiologist or radiological technologist, as is the case with ROC analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Kubota et al [9] called this function the sensitivity spectrum, and they showed that the amount of screen fluorescence could be obtained by integrating the product of the sensitivity spectrum with the incident bremsstrahlung X-ray photon spectrum. In a previous paper [10], we proposed a new method for calculating the sensitivity spectrum theoretically by taking the mass energy-absorption coefficient and the mass loading of the phosphor into account. This confirmed that the X-ray energy absorbed by the layer of phosphor was proportional to the amount of screen fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…[107,67,90]) is beyond the scope of this review as are studies that use psychophysics, e.g. to determine the optimum tube voltage [10] or to aid the detection of abnormalities by measuring visual dwell [106,144]. Similarly we shall not go into detail about studies that quantify the performance of radiologists, usually through observer studies, when image quality parameters of the chest radiographs are varied (e.g.…”
Section: Chapter 2 Computer Analysis Of Chest Radiographs -A Reviewmentioning
confidence: 99%
“…Second, the habitus and level of inspiration of the subject during the examination have a profound impact on the image. Third, the settings of the chest unit, particularly the peak tube voltage, determine how well bony structures are visible [10]. But finally, and most importantly, radiographs are projection images and thus contain superimposed structures.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%